2016
DOI: 10.1097/rli.0000000000000294
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renal Function on Gadolinium-Related Signal Increases on Unenhanced T1-Weighted Brain Magnetic Resonance Imaging

Abstract: Hemodialysis patients receiving linear GBCA have greater dentate nucleus signal increases on unenhanced T1-weighted images, suggesting that renal function may affect the rate of gadolinium accumulation in the brain after linear GBCA-enhanced magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 41 publications
3
27
0
1
Order By: Relevance
“…What is currently known, is that gadolinium is retained in body tissues, regardless of renal function or even GBCA stability [5][6][7][8][9]. Higher concentrations appear to occur in patients with renal impairment [40] or after exposure to the less stable GBCAs [41,42]. This entity of simple retention in tissues has been recently termed "gadolinium storage condition (GSC)" [29].…”
Section: Gadolinium Storage Conditionmentioning
confidence: 99%
“…What is currently known, is that gadolinium is retained in body tissues, regardless of renal function or even GBCA stability [5][6][7][8][9]. Higher concentrations appear to occur in patients with renal impairment [40] or after exposure to the less stable GBCAs [41,42]. This entity of simple retention in tissues has been recently termed "gadolinium storage condition (GSC)" [29].…”
Section: Gadolinium Storage Conditionmentioning
confidence: 99%
“…T1-weighted hyperintensity in the dentate nucleus has been shown recently to occur at lower cumulative doses of linear agents in patients on dialysis than in prior studies of patients with normal renal function. 46 Evidence-from both clinical and preclinical studies-to date favors that patients with impaired renal function are at higher risk for gadolinium accumulation in the brain and in bone, with this conclusion applying only to the group of agents that have such gadolinium deposition, the linear chelates. 34 Both cited studies furthermore noted deposition of gadolinium in the choroid plexus (beyond what was previously established, specifically the dentate nucleus and the globus pallidus).…”
Section: Minimizing Riskmentioning
confidence: 99%
“…One possible pathway for gadolinium entering the brain might be passage of GBCAs directly from blood into the cerebrospinal fluid (CSF). Recently, Cao et al [26] reported on the renal function effect on gadolinium-related signal increase on unenhanced T1-MRI, and found a trend toward increased choroid plexus signal intensity after GBCA exposure, which also supports this hypothesis.…”
Section: Quantitative Ratios Measurementsmentioning
confidence: 61%
“…Cao et al [26] recently demonstrated that the dentate T1 signal increase occurring in hemodialysis patients was significantly higher compared with that of control subjects matched for age, sex, and GBCA exposure; suggesting that the longer exposure to GBCAs, due to longer dwell time, leads to a greater effect on the DN in renal failure patients. Fortunately, all published studies either used abnormal kidney function as an exclusionary factor in their analysis or conducted careful controlled for kidney function to ensure that any gadolinium deposition in the brain was not caused by deficient clearance of GBCAs by the kidneys [31].…”
Section: Population Variabilitymentioning
confidence: 99%